1997
DOI: 10.1093/infdis/175.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Induces Selective Production of the Chemokine RANTES by Upper Airway Epithelial Cells

Abstract: The presence of histamine and eosinophil cationic protein in nasopharyngeal secretions of infants with respiratory syncytial virus (RSV)-induced bronchiolitis implies the activation of basophil and eosinophil leukocytes, but the specific mechanism of their recruitment has not been elucidated. Chemokines are potent and selective leukocyte chemotactic molecules that are also expressed by airway epithelial cells. Therefore, the pattern of chemokines produced in response to RSV infection was investigated in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
119
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 44 publications
4
119
3
Order By: Relevance
“…In addition, Kirchhoff et al (36) have shown that IRF-1 could activate NF-B, which then synergized with IRF-1 to induce IFN-␤ gene expression. Expression of the RANTES gene has been demonstrated to be stimulated by inflammatory cytokines (37,38), LPS (39), T cell activation (40), and viral infection (41,42). Recently, it has been demonstrated that IRF-3 plays a key role in the activation of RANTES transcription by viral infection (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kirchhoff et al (36) have shown that IRF-1 could activate NF-B, which then synergized with IRF-1 to induce IFN-␤ gene expression. Expression of the RANTES gene has been demonstrated to be stimulated by inflammatory cytokines (37,38), LPS (39), T cell activation (40), and viral infection (41,42). Recently, it has been demonstrated that IRF-3 plays a key role in the activation of RANTES transcription by viral infection (43).…”
Section: Discussionmentioning
confidence: 99%
“…Serum and mucosal secretions were collected on days 0, 7, 14, and 21 for OVA-specific Ab analysis by ELISA. Mice were sacrificed by CO 2 inhalation 1 wk after the last immunization to quantify the OVA-specific Ab-forming cells (AFCs) 3 and T cell responses present in immune compartments.…”
Section: Sample and Tissue Collectionmentioning
confidence: 99%
“…Recently, human nasal-and adenoid-derived epithelial cells have been shown to secrete chemokines such as IL-8, monocyte chemoattractant protein-1 and RANTES in response to infection with respiratory syncytial virus (3,4). RANTES is a CC chemokine that binds CCR1, CCR3, CCR4, and CCR5 and is produced by epithelial cells (3)(4)(5)(6)(7)(8), lymphocytes (9,10), and platelets (11), and acts as a potent chemoattractant for monocytes (12,13), NK cells (14), memory T cells (12,13,15), eosinophils (11), dendritic cells (16), and basophils (17). In addition, RANTES and other chemokines can selectively activate their corresponding lymphoid cell targets (14, 18 -21).…”
mentioning
confidence: 99%
“…Rather, infections, including respiratory viruses, may be more likely to be involved in the pathophysiology of late-onset asthma through host response mechanisms [3]. Viral infections are associated with most exacerbations of asthma and chronic obstructive pulmonary disease (COPD) [4][5][6][7][8], and the most prominent aspect of the epithelial immune response towards viral respiratory infections consists of the production and release of CCL5 [9][10][11][12]. Indeed, exacerbation of mild COPD is associated with the upregulation of CCL5 in both the inflammatory and epithelial cells of the bronchial mucosa [11,13].…”
mentioning
confidence: 99%